Tartrate resistant acid phosphatase 5 (TRAP5) mediates immune cell recruitment in a murine model of pulmonary bacterial infection - Tanner, Lloyd; Bergwik, Jesper; Bhongir, Ravi K. V.; Puthia, Manoj; Lång, Pernilla; Ali, Mohamad N.; Welinder, Charlotte; Önnerfjord, Patrik; Erjefält, Jonas S.; Palmberg, Lena; Andersson, Göran; Egesten, Arne (Frontiers in Immunology, 2022)
During airway infection, upregulation of proinflammatory cytokines and subsequent immune cell recruitment is essential to mitigate bacterial infection. Conversely, during prolonged and non-resolving airway inflammation, neutrophils contribute to tissue damage and remodeling. This occurs during diseases including cystic fibrosis (CF) and COPD where bacterial pathogens, not least Pseudomonas aeruginosa, contribute to disease progression through long-lasting infections. Tartrate-resistant acid phosphatase (TRAP) 5 is a metalloenzyme expressed by alveolar macrophages and one of its target substrates is the phosphoglycoprotein osteopontin (OPN). In this study, we found that Trap5-/- mice had impaired clearance of P. aeruginosa airway infection and reduced recruitment of immune cells (i.e. neutrophils and inflammatory macrophages). Trap5 knockdown using siRNA resulted in a decreased activation of the proinflammatory transcription factor NF-B in reporter mice and a subsequent decrease of proinflammatory gene expression. Add-back experiments of enzymatically active TRAP5 to Trap5-/- mice restored immune cell recruitment and bacterial killing. In human CF lung tissue, TRAP5 of alveolar macrophages was detected in proximity to OPN to a higher degree than in normal lung tissue, indicating possible interactions. Taken together, the findings of this study suggest a key role for TRAP5 in modulating airway inflammation. This could have bearing in diseases such as CF and COPD where excessive neutrophilic inflammation could be targeted by pharmacological inhibitors of TRAP5.